2013
DOI: 10.1242/bio.20135991
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Arabidopsis RPK1 gene uncouple cotyledon anlagen and primordia by modulating epidermal cell shape and polarity

Abstract: SummaryPlant seedlings have either one or two cotyledons. The mechanisms that regulate this organ number are poorly understood. Mutations in the RECEPTOR-LIKE PROTEIN KINASE1 (RPK1) gene of the dicot Arabidopsis have only one cotyledon, with low penetrance due to complex genetic redundancy. An analysis of patterning genes required for cotyledon initiation showed that these have normal expression patterns, defining the cotyledon anlagen, in rpk1. This was also true for key genes, which organize the shoot apical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…The auxin efflux carrier PIN-FORMED1 (PIN1) is not expressed in the defective half of the embryos lacking one cotyledon primordium, correlating with an absence of auxin maxima. A link between misregulated polarity of PIN1 in the epidermis of rpk1 and the occurrence of plants with one cotyledon was also recently demonstrated in the rpk1 embryos with cotyledon defects (Luichtl et al 2013).…”
mentioning
confidence: 69%
“…The auxin efflux carrier PIN-FORMED1 (PIN1) is not expressed in the defective half of the embryos lacking one cotyledon primordium, correlating with an absence of auxin maxima. A link between misregulated polarity of PIN1 in the epidermis of rpk1 and the occurrence of plants with one cotyledon was also recently demonstrated in the rpk1 embryos with cotyledon defects (Luichtl et al 2013).…”
mentioning
confidence: 69%
“…Importantly, single rpk1 mutants exhibit a recalcitrant shoot regeneration phenotype, and hence, in contrast to its role in embryogenesis, RPK1 plays an autonomous role in shoot organogenesis. Finally, several aspects described for RPK1 during embryo formation (36,46,48) support its involvement in regeneration: (i) RPK1 expression is important for PINFORMED1 localization, which is required for the establishment of auxin maxima, (ii) an RPK1-dependent pathway is thought to initiate WUS-RELATED HOMEOBOX5 expression, and (iii) RPK1 is assumed to receive intercellular signals and mediate intracellular responses required for pattern formation. Indeed, correct PINFORMED1 localization and auxin maxima are necessary for the initiation of shoot regeneration (21,55,56), WUS-RELATED HOMEOBOX5 expression is associated with shoot primordium formation (18), and patterning is clearly an essential phase in the establishment of shoot primordia in root tissues (21,56).…”
Section: Discussionmentioning
confidence: 98%
“…RPK1 has been reported to function upstream of abscisic acid (ABA) signaling (44) and be involved in diverse processes, such as stress tolerance, senescence, embryonic patterning, and formation of cotyledon primordia (34,36,(45)(46)(47)(48). Assessment of the regeneration rate of two rpk1 mutants in the Col-0 background clearly showed the importance of this gene in regeneration, assigning an additional function to RPK1.…”
Section: Discussionmentioning
confidence: 99%
“…RPK1 was identified to be upregulated by ABA and abiotic stresses (Hong et al, 1997) and has been shown to function as a positive regulator of ABA signaling (Osakabe et al, 2005(Osakabe et al, , 2010. Furthermore, RPK1 plays important roles in other developmental processes, including age-dependent cell death (Lee et al, 2011), embryonic pattern formation (Nodine et al, 2007), shoot regeneration (Motte et al, 2014), and cotyledon development (Luichtl et al, 2013). It is uncertain whether ABA, via RPK1, is involved in these developmental processes, but RPK1 in senescence has been shown to depend on ABA (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%